5-HT2A receptor-mediated PKCδ phosphorylation is critical for serotonergic impairments induced by p-chloroamphetamine in mice. (July 2020) - Phan, Dieu Hien; Shin, Eun-Joo; Sharma, Naveen; Hoang Yen, Tran Phi; Dang, Duy-Khanh; Lee, Yong Sup; Lee, Yu Jeung; Nah, Seung-Yeol; Cheong, Jae Hoon; Jeong, Ji Hoon; Kim, Hyoung-Chun
Abstract: p -Chloroamphetamine (PCA), an amphetamine derivative, has been shown to induce serotonergic toxicity. However, the precise mechanism of serotonergic toxicity induced by PCA remains unclear. In this study, PCA treatment (20 mg/kg, i.p.) did not significantly change 5-HT1A receptor gene expression, but significantly increased 5-HT2A receptor gene expression. Furthermore, 5-HT2A receptor antagonist MDL11939, but not 5-HT1A receptor antagonist WAY100635, significantly attenuated PCA-induced serotonergic impairments. We investigated whether PCA activated a specific isoform of protein kinase C (PKC), since previous evidence indicated the involvement of PKC in neurotoxicity induced by amphetamines. We observed that PCA treatment significantly increased the expression levels of PKC δ among all PKC isoforms. MDL11939 treatment significantly attenuated PCA-induced phosphorylation of PKC δ . However, PCA-induced increase in 5-HT2A receptor gene expression was not altered by rottlerin (a pharmacological inhibitor of PKC δ ) in mice, suggesting that 5-HT2A receptor is an upstream molecule for the activation of PKC δ . Rottlerin or PKC δ knockout significantly attenuated serotonergic behaviors. However, MDL11939 did not show any additional effects against the attenuation caused by PKC δ knockout in mice, suggesting that PKC δ gene is a molecular target for 5-HT2A receptor-mediated serotonergic effects. Our results suggest that 5-HT2A receptor mediates PCA-induced serotonergic impairments via activation of PKC. δ . Graphical abstract: Image 1 Highlights: A high dose of PCA markedly increased hypothalamic 5-HT2A receptor (R) expression. 5-HT2A R antagonism protected against PCA-induced phosphorylation of PKCδ. The phosphorylation of PKCδ mediated PCA-induced serotonergic impairments. Pharmacological/genetic inhibition of PKCδ rescued these serotonergic impairments.